A study on student satisfaction in relation to building maintenance practice at a residential college / Mohamad Noor Rizlan Roslan and Mohamad Haszirul Mohd Hashim - Roslan, Mohamad Noor Rizlan; Mohd Hashim, Mohamad Haszirul (2023)
The aim of this study is to analyse the maintenance management practices at student hostel. A number of studies have investigated the maintenance management of buildings, however, most of the studies have observed maintenance management procedures that were corrective and condition-based. Although this research is specifically proposed for university buildings, however, many public and private sector institutions face similar maintenance management problems. Therefore, this research has broader applications. This research emerged from the need for an alternative building maintenance management system that reflects current thinking on the efficient and effective use of maintenance resources. The first approach used in this study is a primary source, which is a questionnaire survey. The questionnaire will be in the form of a Google Form, and the link will be circulated via media platforms such as Email and WhatsApp, with clear and straightforward questions. The researcher has made some small changes to the questionnaires based on the study's research purpose and research question. The researcher will record the replies as samples of data collecting based on the answers supplied later in the findings. It was found that the implementation of an effective maintenance management system is crucial for the smooth functioning and upkeep of student hostels. This study on student satisfaction with hostel maintenance management has provided valuable insights into the perceptions and experiences of students regarding the maintenance practices in their hostels. Through careful analysis of the data, several key findings have emerged, contributing to our understanding of this important area.